Optimization of oxygen doped of copper (I) iodide (Cul) thin films for dye-sensitized solar cell / Nor Asiah Othman - Othman, Nor Asiah (2013)
In this research, a new approach for depositing Cul thin films using the mister atomizer technique has been used. The wide band gap p-type semiconductor of Cul thin film was prepared by mixing the 0.05M Cul powder with 350 ml of acetonitrile as a solvent. The argon gas was used as a carrier gas with constant flow rate of 12ml/min. The substrate temperature was controlled about the range of 70°C-80°C. Oxygen gas also has been used as a dopant to the deposited Cul thin films by using the Chemical Vapor Deposition with the controlled of oxygen flow rate. The results show that the nanostructured particles of Cul has been developed my mister atomization technique. The conductivity also increases by dope the oxygen into the Cul thin films. The surface morphology characterized by FESEM shows a uniform thin film using this deposition technique. The energy band gap deposited by mister atomizer is smaller than the reported band gap of 3.1 eV. The smaller band gap gives better energy utilization for bigger solar cell spectrum.